PENYULUHAN NARKOTIKA DI PESANTREN AN-NAHDHLAH MAKASSAR - St. Maryam; Rahmawati; Rais Razak; Andi Emelda; St Maryam; Irma Santi; Rezky Amriati Syarif (JURNAL PENGABDIAN MASYARAKAT YAMASI, 2025)
In recent decades, drug abuse has had a very high prevalence. Drug abuse has become a global issue. Its distribution is increasing and supported by the use of advanced technology. The deviation in drug use in Indonesia is already at a very urgent position that needs to be addressed immediately. The ease of drug distribution and use among young people is closely related to the neglect of values, norms, rules, and laws that apply in their social environment. This Community Service aims to provide counseling to third-year students of Madrasah Aliyah Pesantren An-Nahdhlah Makassar about the types, benefits, and dangers of drug abuse in society. The transfer of material was conducted using the method of direct counseling to the PkM partners at the school. The results of the activity included an increase in the partners' knowledge and understanding of the types, benefits, and dangers of drug abuse. Based on the results of the pre and post-test evaluations conducted with the partners, an increase in understanding of the material by 30% was achieved.